Nutrition Reconciliation and Nutrition Prophylaxis: Toward Total Health - Tuso, Phillip (Perm J, 2015)
Malnutrition is a common and debilitating condition in the acute hospital setting that is associated with many adverse outcomes, including prolonged length of hospital stay, increased readmission rates, and increased mortality. However, malnutrition by definition may be an abnormality in either under- or overnutrition. With obesity rates rising, many patients admitted to the hospital may be overnourished from unhealthy eating habits. Unhealthy eating habits and obesity increase a patient’s risk for cardiovascular events and complications in the hospital setting. Nutrition risk screening or nutrition reconciliation is an underutilized tool in the hospital that would identify patients with over- and undernutrition. Nutrition intervention or nutrition prophylaxis initiated in the hospital may help reduce hospital days, readmissions, and mortality. Nutrition reconciliation is a new term developed to increase the awareness of nutrition in total health. Nutrition reconciliation means that all patients have their nutritional status reconciled on admission to and discharge from the hospital. Nutrition reconciliation is defined as the process of maximizing health by helping align an individual’s current diet to the diet prescribed for him or her by the health care team. Nutrition prophylaxis is a proactive intervention to prevent a medical complication. Mandatory nutrition reconciliation and nutrition prophylaxis is not widely performed in most hospitals. Such an intervention may help our patients by improving their short-and long-term health. In addition, nutrition reconciliation and nutrition prophylaxis may allow for a more effective use of resources to prevent a preventable disease.